Peningkatan Kualitas Produk Makanan pada UKM di Kota Magelang - Rany Puspita Dewi; Trisma Jaya Saputra; Herru Santosa Budiono (Warta LPM, 2023)
Small Medium Enterprise (SME) Keripik Talas “Sumber Rejeki” is placed approximately 3.6 km from Magelang and produces taro chips. It has been started production in 2010. One of the production processes that is still done traditionally, is oil draining, so the taro chips produced still have high oil content. The purpose of the activity is to escalate the productivity of SME "Jaya Makmur". The activity was done in two phases in Cacaban, Magelang. The first activity began by collecting documentation data and discussion with partner, Mrs. Tuminem. The second acitivity was continued by developing the completion process, application of spinner machine. Measurement the enhancement in productivity is done by measuring the capacity and quality of the chips produced and measurement the enhancement in income is done by calculating the profit before and after the application of the spinner machine. The activity produced the main output, the appropriate technology, that is the spinner machine which capacity of 12 liters and a power of 60 watts and also is equipped with a speed controller and timer. The use of the spinner able to escalate the output capacity which at first 20 kg/day became 40 kg/day with lower oil content. Besides that, it is also able to increase the profits up to 5 times the profits obtained previously.